Hubungan Umur dan Paritas Dengan Kejadian Retensio Plasenta Pada Ibu Bersalin di Puskesmas Sonomartani Labura Tahun 2023 - Christin Rimeta Lubis; Ester Simanullang; Nur Azizah (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Vaccination actively seeks to create/increase a person's immunity against disease. Vaccination protects children from several immunization-preventable diseases (VPD). The aim of this study is to determine the relationship between age and parity and the incidence of retained placenta in mothers giving birth at the Sonomartani Labura Health Center in 2023. The population in this study includes all women giving birth with retained placenta and recorded in the medical records in January 2022-December 2022 at the Sonomartani Labura Health Center as many as 16 patients. Data analysis using univariate, bivariate analysis. The results of this study show the relationship between age and parity and the incidence of retained placenta in mothers giving birth at the Sonomartani Labura Community Health Center in 2023.